Development of Flipping Book Media Based on Self-Management to Improve Discipline of Slow Learner Students - Saraswati, Retno; Widajati, Wiwik; Pamuji, Pamuji (Universitas Negeri Malang, 2025)
This study aims to develop Flipping book media in behavioral self-management counseling to improve the discipline of slow learner students. The media is utilized within behavioral counseling services. The research method employed is the ADDIE development model, which consists of five stages: Analysis, Design, Development, Implementarion, and Evaluation. The research subjects were slow learner students experiencing difficulties in learning discipline. Data were collected through observation, interviews, and questionnaires. The validity test results conducted by media experts, material experts, and practitioners indicate that the web-based flipping book media is feasible and valid for use. Effectiveness analysis using the Wilcoxon Signed Rank test shows a significant difference before and after the intervention. Thus, the use of flipping book media in behavioral self-management counseling services is proven effective in improving the discipline of slow learner students.